Next‐generation sequencing of endoscopic ultrasound guided microbiopsies from pancreatic cystic neoplasms. Issue 5 (6th September 2019) - Vestrup Rift, Charlotte; Melchior, Linea C; Kovacevic, Bojan; Toxværd, Anders; Klausen, Pia; Karstensen, John G; Kalaitzakis, Evangelos; Storkholm, Jan; Palnæs Hansen, Carsten; Vilmann, Peter; Preuss Hasselby, Jane
Abstract : Aims: Interpretation of cytology samples from pancreatic cysts is challenging. A novel microbiopsy forceps used during endoscopic ultrasound examinations offers new opportunities for histological examination of tissue from pancreatic cysts as well as next‐generation sequencing. The aim of this study was to analyse the results of next‐generation sequencing of microbiopsies from pancreatic cysts. Methods and results: Microbiopsies from 27 patients were obtained, 23 of which were subjected to next‐generation sequencing. Sixteen intraductal papillary mucinous neoplasms harboured mutations in genes regulating cell cycle and repair, and three were without mutations. Most frequent mutations were found in the KRAS and GNAS genes, and these were often concomitant. Three serous cystic neoplasms were without mutations, while with regard to histology, a non‐diagnostic microbiopsy harboured a KRAS and a TP53 mutation and was deemed malignant after clinical follow‐up. Three patients underwent surgery, and the point mutations detected in the microbiopsies were confirmed in the resected specimens. We identified one resected sample with an additional GNAS mutation which was not identified in the microbiopsy. Conclusions: Next‐generation sequencing of microbiopsies may have the potential to improve diagnostic decision‐making.